PERENCANAAN PENAMBANGAN JANGKA MENENGAH (QUARTERLY PLAN) NIKEL LATERIT PADA PIT A, B DAN C PT. GANE PERMAI SENTOSA HARITA NICKEL PULAU OBI, MALUKU UTARA - Annisa Intan Y.R; Dedi Yulhendra; Adree Octova (Journals Mining Engineering : Bina Tambang, 2014)
PT. Gane Permai Sentosa (Nickel Harita Group) is one of the private mining companies that are conducting nickel laterite mining in Obi island, South Halmahera, North Maluku Province. PT. Gane Permai Sentosa is using open pit mine as its mining method. Of the block models that has been estimated by krigging method, there are 1,215,946 tons of mineable reserve ore which is the result of blending between high grade ore with 2.02% of Ni grade which has the portion 67% in total of mineable reserve and medium-grade ore with 1,60% Ni grade which has 33% in total of mineable reserve. That will be blanded and will reach 1.90% grade of Ni and the average stripping ratio is 1.57 and can be mined for 6 month. With the production target of ore is 200,000 tonnes in a month as like as buyer spesification that minimum Ni grade is 1.85% We can conclude that for the medium term mining in Pit A, B and C will be able to be mined and reach production targets set.  Keywords: reserve calculation, production schedulling, ore analysis